Efavirenz restored NMDA receptor dysfunction and inhibited epileptic seizures in GluN2A/Grin2a mutant mice - Zhao, Teng; Zhong, Rui; Zhang, Xinyue; Li, Guangjian; Zhou, Chunkui; Fang, Shaokuan; Ding, Ying; Lin, Weihong (Frontiers in Neuroscience, 2023)
Introduction N-methyl-D-aspartate receptor (NMDAR) is one of the main receptor of the excitatory neurotransmitter glutamate in the brain, which is the key determinant of the excitatory/inhibitory balance of neural network. GluN2A/GRIN2A is one of the subunits of NMDAR and plays an important role in epilepsy. Approximately 78% of patients with GluN2A/Grin2a mutations have epilepsy, and the underlying mechanism of this association is not well characterized. Methods We constructed a mouse model of hyperthermic seizure, and conducted in vitro and in vivo electrophysiological and behavioral studies to clarify the pathogenic characteristics and mechanism of GluN2A/GRIN2A-V685G mutation. In addition, the drug efavirenz (EFV), which is used to treat HIV infection, was administrated to mutant animals to assess whether it can restore the loss of function. Results Mutant mice showed no significant change in the mRNA or protein expressions of NMDAR compared with wild type (WT) mice. Mice with GluN2A/GRIN2A-V685G mutation exhibited shorter latency to seizure, increased frequency of seizure-like events, decreased peak current and current area of NMDAR excitatory postsynaptic current, and decreased event frequency of micro-inhibitory postsynaptic current, compared to WT mice. They also exhibited decreased threshold, increased amplitude, increased input resistance, and increased root number of action potential. EFV administration reversed these changes. The loss-of-function (LoF) mutation of NMDAR changed the excitatory/inhibitory balance of neural network, rendering animal more prone to seizures. Discussion EFV was indicated to hold its potential in the treatment of inherited epilepsy.